Analisis Total Quality Management (TQM) dalam Manajemen Operasional di Intanaya Tour and Travel Cabang Surabaya - Purnama, Siska; Maesaroh, Imas (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2021)
This study is to determine and analyze the concept of Total Quality Management and its implementation in the Surabaya Branch of Intanaya Tour and Travel. Researchers used descriptive qualitative methods. The results of the study illustrate that the concept of Total Quality Management in Intanaya Tour and Travel is a customer value strategy in the form of a questionnaire strategy and business planning in congregational mapping. Secondly, an organizational system in the form of employees who focus on providing customer value, a communication system that upholds service quality and a leader control system for employees. Thirdly, quality improvement at Intanaya Tour and Travel in the form of planning by the manager. The implementation of Total Quality Management at Intanaya Tour and Travel has three phases: preparation, planning and implementation. It includes an operational manager who focuses on quality control, the application of PDCA (Plan-Do-Check-Adjust) activities in the quality control system and an evaluation system for employees and congregational services.